Synthesis of Novel Benzothiazinedione - Habibi, Davood; Aarezi, Fatemeh (Asian Journal of Chemistry, 2010)
3,4-Dihydro-2H-benzo[b][1,4]thiazine-6,7-dione was synthesized from the reaction of cysteamine with catechol in the presence of potassium hexacyanoferrate(III) in 9 different pHs. Structural elucidations by spectro-scopic methods showed that the same product was produced in different acidic and basic pHs.